2002
DOI: 10.1097/00004703-200210000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Children’s Cortisol Activation During the Transition to Kindergarten

Abstract: The purpose of the present study was to identify predictors of children's cortisol responses after the transition to kindergarten. Morning salivary cortisol was measured in 50 children 1 week before and 1 week after they began kindergarten. Children who experienced a greater degree of change between their preschool and kindergarten routines and who had infrequent preschool experiences exhibited the largest increases in morning cortisols after kindergarten entry. Children whose parents indicated that they would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 47 publications
3
30
0
1
Order By: Relevance
“…The authors argue that self competence in novel/social situations reflects both ability to regulate emotion and elicits less fear of approaching such situations, further increasing levels of self competency (Schmidt et al 1999). It is worth noting that parental expectations of the transition experience, as related to the parents' assessment of their child's ability to cope with the transition from preschool to kindergarten, also appear to have an influence on morning cortisol levels (Quas et al 2002). As noted, the majority of this preschool and school transition research to date has been conducted in the United States (US).…”
Section: Physiological Responsivity In School Transitionmentioning
confidence: 99%
“…The authors argue that self competence in novel/social situations reflects both ability to regulate emotion and elicits less fear of approaching such situations, further increasing levels of self competency (Schmidt et al 1999). It is worth noting that parental expectations of the transition experience, as related to the parents' assessment of their child's ability to cope with the transition from preschool to kindergarten, also appear to have an influence on morning cortisol levels (Quas et al 2002). As noted, the majority of this preschool and school transition research to date has been conducted in the United States (US).…”
Section: Physiological Responsivity In School Transitionmentioning
confidence: 99%
“…For example, Wildenger et al (2008) found that less than 75% of their sample of families were on time with important routines such as dinner time and bed time. Additionally, Quas et al (2002) reported that children who experienced the greatest degree of change in their routines between preschool and kindergarten evidenced the greatest amount of physiological stress. Consistent routines are hypothesized to be vital for children to be able to establish a sense of security, trust, and independence (Sytsma et al 2001).…”
Section: The Kindergarten Transitionmentioning
confidence: 99%
“…This sudden shift in daily routines seems likely to heighten the stress associated with transition for both parents and children. This assertion is supported by the research of Quas et al (2002) examining predictors of child stress during the transition to kindergarten. An important aspect of change considered by parents was a shift in child routines in kindergarten.…”
Section: Discussionmentioning
confidence: 80%
“…In particular, children are faced with increased academic expectations, a more formal, inflexible classroom environment, reduced teacher attention, generally more complex social interactions, and decreased family involvement and connection with the school in kindergarten (Pianta and Kraft-Sayre 2003). Consistent with this explanation, a study that examined predictors of children's stress reactivity during the transition to kindergarten as measured by changes in morning cortisol levels, found that children who experienced a greater degree of change between their preschool and kindergarten routines experienced more physiological stress (Quas et al 2002).…”
Section: Routines and The Kindergarten Transitionmentioning
confidence: 88%